Profiling Indonesian Vocational Students' English Communicative Competence: An Analysis of ELT Syllabus Implementation - Hidayani, Selnistia; Oktaviana, Fadilla; Heryatun, Yayu; Assapari, Muhammad Mughni (Universitas Pendidikan Mandalika, 2025)
Vocational schools provide practical training and technical education for various professions, such as automotive, construction, engineering and healthcare. Language skills are essential for competitiveness in the global era, as students use oral or written communication to share information and experiences. The purpose of this study was to determine the level of communicative competence, needs, and ways to develop students' competence. This research is a descriptive qualitative study that collected data from sixty students, three English teachers, and two officers. The study found that the communicative competence profile of private vocational school students is still low. Some of the factors that influence this condition are teachers' commitment and knowledge, students' competence, and school facilities. In order to be employed by the business world, graduates of private SMK must have several important abilities such as speaking, writing, reading, and have a good understanding of computer languages. These skills are essential to ensure that graduates can create official documents needed in the workplace, understand words and procedures, and communicate effectively. As a result, the growth of these skills will make graduates of private vocational schools more capable and readier to enter the workforce.